Institutional efforts and regional distribution of Climate-Smart Agriculture (CSA) initiatives in Ghana - Dziwornu, Michael Gameli; Mponela, Powell; Inusah, Sandra Sawdiatu; Agyarko, Fred Fosu; Yeboah, Stephen; Damba, Osman Tahidu; Akpatsu, Isaac Boatey; Abera, Wuletawu (Elsevier, 2025)
Mapping climate-smart agriculture (CSA) initiatives enable countries to account for emissions and develop adaptation measures. While discourse on CSA implementation exists, developing countries lack empirical evidence to support intervention design. This study analyzes actor networks and assesses social benefits through a comprehensive review of 153 CSA projects across Ghana's 16 regions from 1971 to 2023. The Northern region hosted the highest concentration (17 %) of CSA projects, followed by Upper West, Upper East, Bono, Eastern, and Ashanti regions, primarily focusing on drought adaptation. Crop production emerged as the dominant system (56%), with governmental entities leading 80.4 % of initiatives. Regional variations show post-harvest loss reduction as the primary aim in southern regions, while forestry and aquaculture initiatives concentrate in Eastern and Western regions to address flood vulnerability in degraded landscapes. The study reveals spatial and temporal patterns in Ghana's CSA implementation, identifying gaps in coverage and stakeholder participation. These findings provide an evidence base for policymakers to optimize resource allocation, strengthen underserved regions' climate resilience, and align CSA initiatives with national sustainable development goals.